Multi-Membership Participation of Young People and Public Sphere: Evidence from Chile - Thezá Manríquez, Marcel; Candia Augusti, Eduardo (Revista del CLAD Reforma y Democracia, 2015)
The aim of this paper is to present a set of reflections, both theoretical and empirical, on the phenomenon of juvenile associative participation and its relationship to the development of greater civility as a condition for strengthening democracy. In this context, this article presents a series of findings on the phenomenon we refer to as “multi-membership” establishing, its theoretical importance, its conceptualization, as well as formulating a proposal to specify its size as an object of study. Moreover its relationship with civic behavior is explored.Thus, the document seeks to determine, first, whether the phenomenon of multi-membership is an instrument of social integration typical of our society’s cultural model; second, what kind of motivations drive and/or discourage young people’s participation in multiple forms; third, if an eventual Multi-Purpose is a widening social and ideological experimentation strategy; and finally, what is the impact of an eventual multi-membership on civic life of young people and the consecuencies on public policies.
Keywords: Social Participation; Citizen Participation; Public Policy; Youth; Chile